Penerimaan Diri dan Subjective Well-Being pada Penyandang Difabel yang Berkarier - Gratia Yahwelin Tumion; Arthur Huwae (Jurnal Ilmu Perilaku, 2023)
Being a disabled person with a career is not easy in living a daily life in the world of work. In the work environment, people with disabilities often experience social inequality. The problems faced make it difficult for people with disabilities to achieve subjective well-being in a career due to poor self-acceptance factors. This study aims to determine the relationship between self-acceptance and subjective well-being in people with disabilities who have a career. The research method used was quantitative with a correlational design. 127 career-disabled people were used as participants in the study using a purposive sampling technique. Research data collection for self-acceptance variables using the Berger Self Acceptance Scale (BSAS) and subjective well-being variables using the Satisfaction with Life Scale (SWLS) and Positive Affect Negative Affect Scale (PANAS). The results of data analysis from the Pearson Correlation value of 0.053 and sig. = 0.283 (p > 0.05) showed that the research hypothesis was rejected, meaning there was no significant relationship with self-acceptance. This indicates that self-acceptance is not one of the factors associated with subjective well-being in people with disabilities who have a career.